Katawan a study on the influence of fashion magazines on a woman's view of her physical self - Derecho, Joanne Y.
Beauty has always been in the eye of the beholder. However, with the advent of the fashion magazines, woman now has a picture of what beautiful should look like. In her attempt to be an epitome of perfection, she subjects herself to endless diets, exercise and body sculpting. Up to what extent does magazines exert their influences on a woman's physical self? This study attempts to answer the above question. It attempts to shed light on the following points: 1) How and when the concept of beauty started, 2) the socio-economic factors that have influenced the way evolution of the concept of beauty, 3) the effect of magazines on a woman's perception of her self, physical body and self esteem, 4) the different industries that have sprouted to be able to meet the demands of women on beauty products. The researchers used content analysis of Mod magazine to be able to find out the evolution of beauty from the 1960's down to the 1990's. In addition to this, a survey was conducted to find out what is the Filipino concept of beautiful today (2000). Textual analysis was used to find out the different industries that have sprouted to meet the demands of women to beautify themselves. Historical analysis of some books written by various Filipino historians helped traced the historical events that have influenced the way beauty was viewed during the decades. Survey and Focus group interviews with the audience (readers of fashion magazines) intended to find out the effect (if any) of magazines on the way they view their physical self. At the same time, the gatekeepers of Mod Cosmopolitan, Preview and Mega were interviewed to be able to find out their opinions about the issue at hand. Results of the study shows the concept of what is beautiful changed from the 1960's to the 1990's. The 1990's showed the rise of the waif look while the nineties were more into the sporty look. It was also found out that MTV VJ Sonia is the embodiment of all the collective traits of what they Filipinos find beautiful today. Women today are affected by magazines only up to a point because there are other media influences at play (there is television, radio, and film) as apparent by their choice of VJ Sonia as the epitome of what they find beautiful in a woman. The gatekeepers and the audience affect each other. The audience exerts itself financially as a consumer. Their buying habits influences what they magazines will put in their next issue. At the same time, the magazines influence the audience when it comes to information because the readers look up to them as their source of information.